Managerial accounting / Ronald W Hilton - Hilton, Ronald W.
The emphasis of this text is to teach students how to use and interpret accounting information in managing an organization. It includes: coverage of contemporary topics; a balanced use of service/retail/non-profit and manufacturing companies; and a company focus per chapter.